Generation Z's Level Of Muslim Understanding On Sharia Capital Market - Nurul Izzah; Sri Sudiarti (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2022)
The growing public awareness of Islamic investment has encouraged the development of the Islamic capital market in Indonesia. Young people in most parts of the world have low levels of financial literacy. This is due to various factors such as socioeconomic and demographic. The low level of Islamic financial literacy is reflected in the low level of public understanding of the Islamic capital market. This study aims to measure the level of understanding of Muslim generation Z on the Islamic capital market. This research is a quantitative research using primary data. The sample of this research is Muslim generation Z, totaling 245 people with purposive sampling technique. Data analysis used in this research is univariate test. The results show that generation Z Muslims are related to the Islamic capital market at a good level of understanding as much as 39 percent, enough as much as 50 percent and less as much as 11 percent. Thus, generation Z Muslims in North Sumatra have a sufficient level of understanding related to the Islamic capital market. Various efforts can be made to increase understanding of Generation Z Muslims through education, outreach, seminars and promotions through social media.